AMD - Current Standard of Care and the Pakistani Perspective - Ali, Azam (Pakistan Journal of Ophthalmology, 2009)
The millennium started with a gift for the evergrowing blind population of the world, especially in the developed world, where age-related macular degeneration (AMD) ranked as the leading cause of unpreventable blindness. Millions were saved from going permanently blind with the onset of new therapies aimed towards preserving and improving vision in these patients. For many years the retina specialists were unable to treat choroidal neovascularization (CNV) in AMD with good visual results. In the early 90’s some success was reported with laser photocoagulation treatment of small classic CNV lesions. But ultimately the concept of foveal photocoagulation which was recommended by the MPS subfoveal study was rejected as the long term results were hopeless.